2016
DOI: 10.1136/bmjopen-2015-009203
|View full text |Cite
|
Sign up to set email alerts
|

Lay support for pregnant women with social risk: a randomised controlled trial

Abstract: Interventions: POWs were trained to provide individual support and case management for the women including home visiting from randomisation to 6 weeks after birth. Standard maternity care (control) included provision for referring women with social risk factors to specialist midwifery services, available to both arms. Main outcome measures: Primary outcomes wereantenatal visits attended and Edinburgh Postnatal Depression Scale (EPDS) 8-12 weeks postpartum. Prespecified, powered, subgroup comparison was among w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 22 publications
1
91
0
Order By: Relevance
“…(15) Other studies primarily focus on the role and impact of peer/volunteer support for socially marginalised women. (9,16,21,23) Whereas our study explores the support provided by both thirdsector volunteers and maternity professionals working collaboratively within hospital and community settings. This partnership approach offers a holistic approach to care which seeks to promote women's wellbeing in the widest sense.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(15) Other studies primarily focus on the role and impact of peer/volunteer support for socially marginalised women. (9,16,21,23) Whereas our study explores the support provided by both thirdsector volunteers and maternity professionals working collaboratively within hospital and community settings. This partnership approach offers a holistic approach to care which seeks to promote women's wellbeing in the widest sense.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Our study also resonates with other research suggesting that offering multi-agency person centred care, in the form of targeted rather than generalised care is key to enabling marginalised women to access and benefit from interventions. (23) The need to identify the theoretical underpinnings of intervention designs is well highlighted in the literature. women's capabilities were increased via needs led information and practical support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibson and Hanson (2013) observe that UK mothers consider Facebook an important aspect of their motherhood because it allows them to be socially connected (see also Kaufmann, Buckner, and Ledbetter 2017). A randomised controlled trial suggested that support of lay workers improves maternal and child outcomes in disadvantaged families (Kenyon et al 2016). Hence, be it through family ties, ethnic associations, or support from lay workers, English mothers find support in paradigms of relatedness in response to perinatal social isolation.…”
Section: Parenting Challenges and Life Chancesmentioning
confidence: 99%
“…The POW’s role was also to provide support to mothers to improve their psychological health, including depression, self efficacy and bonding. Most contacts between POWs and the women in the trial took place antenatally (77%), with 27% being face to face contact and half of contacts lasting between 1–2 hours (see http://dx.doi.org/10.1136/bmjopen-2015-009203 [ 38 ] for full trial details). The trial found modest positive effects on maternal mental health at 8–12 weeks postpartum, particularly in those women with greater social risk [ 38 ] and a significant benefit for mother-to-infant bonding.…”
Section: Introductionmentioning
confidence: 99%